IDENTIFIKASI PENGATURAN ZONASI KONSERVASI GUMUK PASIR PARANGTRITIS BERDASARKAN PERTIMBANGAN ANALISA TAPAK (SPASIAL), PERSEPSI DAN ASPIRASI MASYARAKAT - , DANANG KUSUMABRATA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The essence of this research attempts to integrate environmental considerations spatial and environmental conditions in the manufacturing community conservation zoning regulation Parangtritis sand dunes . The following details the purpose of this study : 1 . Identify the zoning regulation in the spatial regulation sand dunes spatially Parangtritis 2 . Knowing the perceptions and aspirations of the local community regarding the benefits / functions of the presence of sand dunes and sand dunes in the zoning regulation Parangtritis 3 . Provide policy direction and strategy needs spatial zoning regulation in the existing land Parangtritis sand dunes . Spatial analysis in this study used to support the identification and zoning regulations . This study uses census method for key informants and snowball sampling method for additional informants . Analysis of the results of the research will be conducted qualitative description that aims to provide a description of the subject of study based on data from the variables obtained through in-depth interviews of the parties involved in the management of sand dune environment. The results of this research note that the development of settlements and uncontrolled vegetation feared sand dune ecosystem damage and inhibit the formation of sand dunes . The development of settlements and vegetation should be controlled so as not to damage the preservation of sand dunes . Core zone should be fully awake naturally . The core areas of need is broken down into subzona - subzona and described landing land use and activities that include a central core zone of the study , the core areas of tourism services , agricultural core zone , core zone of protection , opening the core zone of the wind and the core area prone to disasters . Community supports the conservation of sand dunes but it should be clear boundaries in real tangible stakes . Expectations of the public in order not to damage the movement of sand dunes and land paddy farming areas sand dunes able to provide additional economic value to the surrounding community . Need to set up a joint secretariat for the strategy of coastal management policies undertaken Parangtritis be integrated . Communication in the form of inter-agency coordination and socialization / agencies and to the community in both the planning and implementation should be maintained.